ANALYZE OF THE EFFECTIVENESS AND VERSATILITY OF THE COMPOSITE RESIN STRATIFICATION TECHNIQUE FOR REHABILITATING AESTHETIC TREATMENT - CLINICAL CASE REPORT - Mendes de Lima, Walkiria; Vilela Maia, Elaine; Helena Mota Corrêa, Nilce; De Oliveira Lucas Mendes, Lays; Camilo Silva Monteiro, Megleine; Malpeli, Livia (Health and Society, 2022)
The search for the patterns of beauty and perfection of dental shapes and dimensions has provided a greater appreciation of the appearance of individuals of all ages, because the media has overestimated aesthetics. The composite resins have mechanical properties suitable for use in all types of cavity preparations. However, there are still concerns when the materials are used in situations of high stress, which can cause fracture of the restoration as well as wear, staining, marginal infiltration, translucency and patient satisfaction. Therefore, the objective of this project is to evaluate the proservation of composite resin in complex aesthetic restorations in anterior teeth, through two clinical cases, diastema closure and reanatomization of conidial teeth performed 6 years ago through Federation Dental International indices. It is concluded that the correct execution allied to the dental anatomy domain and knowledge of the properties of the composites achieved satisfactory results that exceeded the expectations of the patients.